Physical aging in glassy mixed matrix membranes; tuning particle interaction for mechanically robust nanocomposite films. Issue 27 (24th June 2016) - Smith, Stefan J. D.; Lau, Cher Hon; Mardel, James I.; Kitchin, Melanie; Konstas, Kristina; Ladewig, Bradley P.; Hill, Matthew R.
Abstract : Addressing the mechanical weakness and physical aging of glassy mixed matrix membranes to realise their potential for enhancing the separation performance of current membrane technologies. Abstract : Despite the exceptional separation performance of modern glassy mixed matrix membranes, these materials are not being utilized to improve the performance of existing membrane technologies. Nano-sized additives can greatly enhance separation performance, and have recently been used to overcome age-related performance loss of high performance MMMs. However nano-additives also compromise the structural integrity of films and little is known on how physical aging affects their mechanical properties over time. A solution for both physical aging and mechanical instability is required before these high performance materials can be utilised in industrial membrane applications. Here, we examine physical aging in mixed matrix membranes through mechanical properties and single gas permeation measurements using three glassy polymers, Matrimid® 5218, poly-1-trimethylsilyl-1-propyne (PTMSP), and a polymer of intrinsic microporosity (PIM-1); and a range of nano-scale additives; silica, PAF-1, UiO-66, and Ti5 UiO-66, each previously shown to enhance gas separation performance. We find polymer-additive interactions strongly influence local physical aging and play a key role in determining the overall material properties of glassy nanocomposite films. Strong interface interactions can slow physical aging, and may not correlate to reinforced or age-stable films. Whereas traditionally 'incompatible' nanocomposites exhibit mechanical properties that can improve over time and even outperform their native polymers. Tuning polymer-additive interactions is vital to achieving the physical aging, mechanical stability, and permselectivity requirements of advanced mixed matrix membrane technologies and reducing the enormous global energy cost of separation processes.